2015
DOI: 10.1017/erm.2015.4
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia signalling manipulation for bone regeneration

Abstract: Hypoxia-inducible factor (HIF) signalling is intricately involved in coupling angiogenesis and osteogenesis during bone development and repair. Activation of HIFs in response to a hypoxic bone micro-environment stimulates the transcription of multiple genes with effects on angiogenesis, precursor cell recruitment and differentiation. Substantial progress has been made in our understanding of the molecular mechanisms by which oxygen content regulates the levels and activity of HIFs. In particular, the discovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 137 publications
(226 reference statements)
1
32
0
Order By: Relevance
“…HIF-1 is a transcription factor composed of 2 subunits, HIF-1α and HIF-1β, and HIF-1α acts as a cellular oxygen sensor that induces a response to low oxygen tension. Activation of the HIF pathway stimulates the transcription of multiple hypoxia response genes, among which VEGF is a major target44. It was reported that simvastatin could protect HIF-1α from degradation by inhibiting prolyl-4-hydroxylase 3 (PHD-3), which hydroxylates the two proline residues in the oxygen-dependent degradation domain of HIF-1α under normoxic conditions and leads to interactions with the von Hippel-Lindau (VHL) ubiquitin ligase complex that promotes ubiquitin-mediated proteolysis of the HIF-1α subunit45.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1 is a transcription factor composed of 2 subunits, HIF-1α and HIF-1β, and HIF-1α acts as a cellular oxygen sensor that induces a response to low oxygen tension. Activation of the HIF pathway stimulates the transcription of multiple hypoxia response genes, among which VEGF is a major target44. It was reported that simvastatin could protect HIF-1α from degradation by inhibiting prolyl-4-hydroxylase 3 (PHD-3), which hydroxylates the two proline residues in the oxygen-dependent degradation domain of HIF-1α under normoxic conditions and leads to interactions with the von Hippel-Lindau (VHL) ubiquitin ligase complex that promotes ubiquitin-mediated proteolysis of the HIF-1α subunit45.…”
Section: Discussionmentioning
confidence: 99%
“…31 In addition to angiogenesis, immobilized DFO may promote osteogenesis through other angiogenesis-independent ways because multiple targets were reported once HIFs signaling pathway was activated. 40,41 Furthermore, many studies reported that hypoxic conditions are able to directly modulate MSC proliferation and differentiation to osteoblasts, though controversial results were noted, which have been summarized in a recent review article. 41 We did not find that DFO could directly increase hMSCs osteogenic differentiation in vitro (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Furthermore, many studies reported that hypoxic conditions are able to directly modulate MSC proliferation and differentiation to osteoblasts, though controversial results were noted, which have been summarized in a recent review article. 41 We did not find that DFO could directly increase hMSCs osteogenic differentiation in vitro (data not shown). Further studies are needed to understand the potential mechanisms by which DFO/HIF-1’s direct effects on MSCs functions for osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The hypoxic microenvironment has been considered as a vital factor for the hypoxia-induced factor (HIF-1)-dependent angiogenesis that is critical for bone formation during bone development and regeneration after trauma [18,19]. Consistently, bone marrow stromal cell differentiation and osteoblastogenesis can be inhibited by hypoxic culture in vitro [20].…”
Section: Discussionmentioning
confidence: 99%